Students' Perceptions of the Use of the Tadoku NPO Website and Picture Storybooks in Tadoku Learning - 'Izzati, Nur (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze and compare students' perceptions of the use of the NPO Tadoku website and picture books as reading media in reading lessons in the Tadoku 2 course. This study uses a quantitative descriptive approach with a questionnaire consisting of 27 closed questions and 8 open questions, covering aspects of ease of use, reading comprehension, material appeal, and reading motivation. The data were analyzed using percentage and descriptive interpretation techniques. The results showed that the NPO Tadoku website received higher ratings in terms of accessibility, reading variety, ease of navigation, and reading comfort. Meanwhile, picture books were rated superior in terms of visual support, clarity of storyline, and physical reading experience. Overall, students preferred digital media because it was considered more practical and in line with current reading habits, although picture books still provided added value, especially in terms of visuals and an enjoyable reading experience. These findings confirm that both media have their own advantages and can complement each other in Japanese reading learning.